Compliance of males with stage 1 testicular germ cell tumours on an active surveillance protocol. Issue 10 (October 2015) - Honeyball, F.; Murali‐Ganesh, R.; Hruby, G.; Grimison, P.
Abstract The aim of this retrospective study was to determine the rate of compliance among 57 males with stage 1 testicular germ cell tumours on an active surveillance protocol at a single Australian centre. At median follow up of 24 months, 81% had adequate compliance with the follow‐up regimen, 12% were lost to follow up, and 16% relapsed; none between protocol visits. Active surveillance is an acceptable alternative to adjuvant therapy for stage 1 testicular germ cell tumours, with reduced toxicity for most and equivalent survival, but requires efforts to maintain adequate compliance with follow up to avoid late detection of recurrence.